The Effects of Foot and Mouth Disease on the Profitability of Smallholder Dairy Farms: Evidence from East Java, Indonesia - Febrianto, Nanang; Hartono, Budi; Nugroho, Eko; Eka Kusumastuti, Anie; Sugeng Winarto, Priyo; Akhiroh, Puji; Susilawati, Trinil; Puspita Anugra Yekti, Aulia; Utami, Putri; Nadia Ramli, Nurul; Helmi, Muhammad (Faculty of Animal Science, Universitas Brawijaya, 2025)
Foot and mouth disease (FMD) poses significant threats to livestock production systems globally, particularly cloven-hoofed animals. Indonesia's recent FMD outbreak, following 35 years of disease-free status, created substantial economic challenges for the dairy sector. Despite the scale of the outbreak, limited research has focused on its specific financial impacts on smallholder dairy farms, creating a critical knowledge gap for effective policy development. This study analyses the financial impact of foot and mouth disease (FMD) on dairy farming, focusing on changes in revenue, costs, and profitability before and after the outbreak. Through descriptive and input?output analysis, economic losses were quantified on the basis of structured surveys and secondary data from affected dairy farmers. The findings indicate that the FMD significantly reduced milk production revenue (-8%) while increasing overall farm costs (+6%), leading to a drastic 84% decline in farm profits. Increased spending on veterinary treatments, feed supplementation, and transportation further exacerbated financial instability, whereas a slight increase in livestock sales (+11%) served as a short-term coping mechanism. These results highlight the need for enhanced disease control measures, financial assistance programs, and policy interventions to support affected farmers. Implementing effective vaccination strategies, improving biosecurity protocols, and establishing government-backed economic relief programs can mitigate the financial burden of FMD on the dairy sector. This study contributes to the limited literature on the economic consequences of livestock disease outbreaks in Indonesia and emphasises the need for long-term resilience strategies to sustain dairy farm profitability and stability in disease-prone regions.